The Influence of Foreland Structures on Hinterland Cooling: Evaluating the Drivers of Exhumation in the Eastern Bhutan Himalaya. Issue 9 (2nd September 2019) - McQuarrie, Nadine; Eizenhöfer, Paul R.; Long, Sean P.; Tobgay, Tobgay; Ehlers, Todd A.; Blythe, Ann E.; Morgan, Leah E.; Gilmore, Michelle E.; Dering, Gregory M.
Abstract: Understanding, and ideally quantifying, the relative roles of climatic and tectonic processes during orogenic exhumation is critical to resolving the dynamics of mountain building. However, vastly differing opinions regarding proposed drivers often complicate how thermochronometric ages are interpreted, particularly from the hinterland portions of thrust belts. Here we integrate three possible cross‐section geometries and kinematics along a transect through the eastern Bhutan Himalaya with a thermal model (Pecube‐D) to calculate the resulting thermal field and predict potential ages. We compare predicted ages to a suite of new and published cooling ages. Our results argue for ramp‐focused exhumation of the Main Central thrust from 16 to 14 Ma at shortening rates of 40–55 mm/year, followed by slower rates (25 mm/year) during the last 50 km of Main Central thrust displacement and growth of the Lesser Himalayan duplex from 14 to 11 Ma. Emplacement of frontal Lesser Himalayan thrust sheets occurred rapidly (55–70 mm/year) between ~11 and 9 Ma, followed by a decrease in shortening rates to ~10 mm/year during motion on the Main Boundary thrust. Modern shortening rates (17 mm/year) and out‐of‐sequence motion on the Main Boundary thrust from 0.5 Ma to present reproduce the young cooling ages near the Main Boundary thrust. We show that the dominant control on exhumation patterns in a fold‐thrust belt results from the evolution of ramps and emphasize that the geometry and kinematics of structures driving hinterland exhumation need to be evaluated with their linked foreland structures to ensure the viability of the proposed geometry, kinematics, and thus cooling history. Key Points: Geometry of structures imparts a first‐order cooling signal to mineral cooling ages Thermochronometers can be used to validate or invalidate balanced cross sections An active hinterland ramp is a dominant driver of young cooling ages in eastern Bhutan